Secularized Secondary School Schematic: Multi-Faith Teaching Etiquette Forecast - Sultan Bagus Firmansyah (Ittishal Educational Research Journal, 2021)
Reacting to the harmonious upon religious pluralism in Indonesia, current educational policies are now supposed to involve a heterogeneous education concept. If based on the common fact, those who keen into pure islamic school, they usually are listed-in Madrasah Secondary School or Madrasah Aliyah. Prior to the pure-islamic school, students whose essence as a christian and/ or catholic, they constantly are enrolled to the Christian or Catholic Secondary School (see SMAK). Aside of them, neither pupils nor parents whose consider religion and ethnic (secular secondary school), their entrance are mostly addressed into the Secondary School itself (the school that hasn’t specify the religious matter). Opposing an existed fact above, this article is trying to exposing the concept of Secularized Secondary School. Such school’s model is prospectable to enhance the multitude of educational path by the Unity in Diversity or Bhinneka Tunggal Ika. A secular senior high school is able to be applied (soon) via multi-religion in Indonesia; 207 million (87%) Moslem; 16.5 million (7,0%) Christian; 6.9 million (2,9%) Catholic; 1.7 million (0,7%) Buddhism; 4 million (1,7%) Hinduism; and 117 thousands (0,05%) Confucianism. The aim of secularized here is equal by the universalized secondary school; which the students are organized by one-united vision above diversities. Such educational policy’s innovation is must be attempted over reconstructing and uniting thirteen-thousands-and-eight-hundred common secondary school around Indonesia.